Breach of confidentiality: unintentional common practice due to misunderstanding and unawareness (Bangladesh Journal of Bioethics, 2012)
Advancement in medical technology has helped man kind in several ways and no one can deny the contribution of medical technology in the field of medicine. On the other hand technology has also given rise to some ethical issues. The issue of confidentiality is one of those issues. Patients keeping their trust on physician reveals all concerned confidential information to their physician with surety that physician will not reveal it to other person and will keep it confidential. It has been common in practice that, physicians unintentionally breach their patients confidentiality by discussing cases and history of their patients in public places, hospital elevators, and with their students. In a busy hospital setting it can be difficult to maintain confidentiality for patients. Increasing workloads lead to discussions of patients in public areas which is not an acceptable excuse. The very next person present there listening the discussion could be a patient's friend, relative, or media member that is not entitled to this privileged information. In all these cases permission must be received from the patient prior to any disclosure.DOI: http://dx.doi.org/10.3329/bioethics.v2i3.10259Bangladesh Journal of Bioethics 2011;2(3):16-18